Pengaruh Bahan Ajar Mikrobiologi Multimedia Terintegrasi STEM (M-STEM) terhadap Kemampuan Berpikir Kritis dan Komunikasi Mahasiswa - Trio Ageng Prayitno; Nuril Hidayati (Universitas Nusantara PGRI Kediri, 2023)
The use of multimedia microbiology teaching materials integrated with STEM to empower students' critical thinking and communication skills has not been carried out optimally. The aim of the study was to determine the effect of STEM (M-STEM) integrated multimedia microbiology teaching materials on students' critical thinking and communication skills. The study method is quasi-experimental through a non-equivalent control group design pretest-posttest research design. The independent variable of the study is M-STEM microbiology teaching materials, and the dependent variable of the study is students' critical thinking and communication skills. The research sample was students from the Biology Education Study Program at IKIP Budi Utomo who were taking a Microbiology course. Class A is the research experimental class and class B is the control class. The research instrument was a multiple-choice type test for pretest and posttest questions. The research data are pre-test and post-test scores from the experimental class and control class which will be tested for prerequisites (normality and homogeneity) first and then will be tested with the ANAKOVA test with SPSS. The results of this study indicate that there is an effect of STEM (M-STEM) integrated multimedia microbiology teaching materials on students' critical thinking skills (sig<0.05) and student communication (sig<0.05). The research concludes that multimedia-integrated STEM (M-STEM) microbiology teaching materials have a positive effect on students' critical thinking skills and communication.